From gut to brain: Deciphering the impact of gut microbiota on neurological health - Gopinath R.; Arundadhi M.; Dhanasezhian A.; Thangam G. Sucila (Novel Research in Microbiology Journal)
The Gut-Brain Axis is a complex and fascinating concept elucidating the two-way communication between gut microbiota and the central nervous system, encompassing diverse mechanisms with profound implications on neurological health. Situated in the gastrointestinal tract, the gut microbiota, a diverse bacterial community, which communicates with the brain through various processes, including neurotransmitter and neuropeptide synthesis, immune system modulation, and involvement of the vagus nerve. These interactions not only impact digestion but also influence emotions, cognition, and behavior. Recent research has revealed the significant influence of gut microbiota on the neurological health, establishing connections between alterations in the gut microbiota composition and the prevailing conditions such as depression and neurodegenerative diseases. This understanding sheds new light on the pathophysiology of neurological disorders, marking the gut-brain axis as an exciting frontier in neuroscience and medicine. The aims of this study were to investigate and elucidate the intricate interplay between the gut microbiota and neurological health, and exploring the mechanisms of communication along the gut-brain axis. As research progresses, the potential for groundbreaking strategies to prevent and treat the neurological disorders becomes increasingly apparent. This comprehensive review delves into the nuanced world of the gutbrain axis, providing insights into the intricate relationship between the gut and the brain. Additionally, this review delves into potential therapeutic implications, exploring the use of probiotics, prebiotics, and dietary interventions to modulate gut microbiota for enhancement of the neurological well-being.